[P194] Breast cancer radiosurgery with a synchrotron radiation beam. (August 2018) - Mettivier, Giovanni; Sarno, Anton io; Di Lillo, Francesca; Masi, Marica; Calandrino, Riccardo; Fiorini, Claudio; Cattaneo, Mauro; Brunetti, Antonio; Fanti, Viviana; Golosio, Bruno; Hoff, Gabriela; Ceresa, Cecilia; et al.
Abstract : Purpose: Recently, we proposed the use of the synchrotron radiation (SR) beam for a new rotational radiotherapy technique for breast cancer treatment (SR 3 T)[1] ;. In this work, we show, via Monte Carlo (MC) simulations, the potential of SR 3 T also for application in breast radiosurgery with the patient in prone position. Methods: We simulated the irradiation condition of the breast rotational radiosurgery with a MC code based on GEANT 4 toolkit. The pendant breast was modeled as a polyethylene cylinder with a diameter of 14 cm and height of 9 cm with a 1-cm tumor simulated in the centre or at 4 cm from the cylinder axis. A monoenergetic laminar SR beam of size 1.5 cm × 1.0 cm with energy ranging between 60 and 120 keV irradiated the phantom during a complete rotation with the center of rotation along the tumor mass. Results: A collimated SR beam irradiating a pendant breast produces a dose distribution peaked at the center of rotation. MC simulations showed that is possible to perform partial-breast irradiation with a skin sparing comparable with that from a conventional MV breast radiotherapy. Conclusions: We proposed a kV SR beam for partial-breast irradiation, for breast radiosurgery in the treatment of small lesions. We foresee the use of dose-enhancement agents in order to improve the dose to the target volume with proper sparing of healthy tissues.